A Systematic Review of Instructional Comparisons in Single-Case Research. (June 2021) - Ledford, Jennifer R.; Chazin, Kate T.; Gagnon, Kari L.; Lord, Anne K.; Turner, Virginia R.; Zimmerman, Kathleen N.
Comparison studies conducted to determine which instructional interventions are most efficient for teaching discrete behaviors to individuals with disabilities are potentially valuable, although some threats to internal validity may be more likely in these studies. Studies included in this review typically met common internal validity standards, such as reliability measurement, but often did not include controls specific to comparison designs. Comparisons often included young children with autism and were frequently conducted by researchers in self-contained classroom settings. Systematic instruction was effective in nearly all comparisons, although many included undifferentiated data (i.e., both interventions were equally effective), and within-participant replications were often inconsistent (i.e., outcomes varied across comparisons for a single participant). Results suggest implementers should conduct high-fidelity instruction with corrective and instructive feedback and should choose intervention variations based on participant preference. We recommend researchers include control sets or time-lagged introductions, counterbalance behavior sets, and measure differential acquisition over time.